1985
DOI: 10.1128/jcm.22.3.369-374.1985
|View full text |Cite
|
Sign up to set email alerts
|

False susceptibility of enterococci to aminoglycosides with blood-enriched Mueller-Hinton agar for disk susceptibility testing

Abstract: Disk diffusion susceptibility tests for enterococci are frequently modified by adding 5% sheep blood (SB) to Mueller-Hinton agar; the performance standards from the National Committee for Clinical Laboratory Standards sanction this addition. Susceptibility testing of aminoglycoside antibiotics is not recommended for enterococci; in actual practice, however, some laboratories do include aminoglycoside antibiotics routinely, and others may test upon request or in selected situations. In examining 50 clinical iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

1988
1988
2000
2000

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…As has been seen by others (16,32), MHA supplemented with sheep blood resulted in larger zones of inhibition than those obtained in unsupplemented agar, a condition which resulted in more false susceptibility, especially for streptomycin. A higher breakpoint could not be used because overlap among the susceptible and resistant strains would have resulted in the opposite condition, i.e., a high percentage of false-positive results for resistance to streptomycin.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…As has been seen by others (16,32), MHA supplemented with sheep blood resulted in larger zones of inhibition than those obtained in unsupplemented agar, a condition which resulted in more false susceptibility, especially for streptomycin. A higher breakpoint could not be used because overlap among the susceptible and resistant strains would have resulted in the opposite condition, i.e., a high percentage of false-positive results for resistance to streptomycin.…”
Section: Discussionsupporting
confidence: 60%
“…In 1984, Pfaller et al (27) confirmed that disks containing the usual 10-g amounts of gentamicin and streptomycin could not distinguish susceptible strains from those with HLR. Jenkins et al (16) showed that when MHA is supplemented with sheep blood, zones of inhibition with 10-g aminoglycoside disks are about 6 mm larger than those when unsupplemented medium is used.…”
Section: Discussionmentioning
confidence: 99%
“…except that 31.6% of laboratories selected Mueller-Hinton agar supplemented with sheep blood as the test medium. Mueller-Hinton agar containing 5% sheep blood was considered acceptable in 1979 and 1983, but NCCLS subsequently recommended Mueller-Hinton agar without supplements when studies demonstrated that the blood in the agar interacted with aminoglycoside disks to yield false-positive results for susceptibility (16). The continued use of this medium by some laboratories raises concerns that outdated practices still occur in clinical laboratories.…”
mentioning
confidence: 99%
“…zone sizes were correlated with the results obtained by the time-kill studies. In addition, because it has been shown in other studies (4,13) that the presence of blood can affect the in vitro susceptibility of enterococci to aminoglycosides, disk tests were performed on Mueller-Hinton agar with and without 5% sheep blood.…”
mentioning
confidence: 99%